Enhancing high school students' mathematical skills: A training program on Winplot for solving quadratic equation - Mayasari, Novi; Indriani, Ari; Noeruddin, Ali; Kholidah, Neneng Rika Jazilatul; Mariana, Dina (Community Empowerment, 2025)
Mathematics is often perceived as a difficult and uninteresting subject, a sentiment shared by students at SMAN 1 Balen. One effective solution to this challenge is the integration of technology-based learning media. The objective of this community engagement program was to train and introduce the Winplot application to students at SMAN 1 Balen to aid in solving quadratic equation problems. This program was conducted in three phases: 1) Preparation, which involved an initial observation of the school to assess needs; 2) Implementation, where training on the use of the Winplot application was delivered through lectures, group discussions, and practical exercises; and 3) Evaluation, to measure the program's effectiveness. The results indicate that 70% of the students were able to competently operate the Winplot application and effectively use it to solve quadratic equation problems. This initiative demonstrates the potential of technology to make mathematics more accessible and engaging for high school students.